2015
DOI: 10.1590/151870122015219
|View full text |Cite
|
Sign up to set email alerts
|

Problemas percibidos y concepciones de extensión de los técnicos del Centro Nacional de Tecnología Agropecuaria y Forestal de El Salvador, Centroamérica

Abstract: La extensión rural se está reposicionando en América Latina como herramienta de desarrollo. 34 extensionistas rurales de El Salvador fueron encuestados para identifi car los problemas a los que se enfrentan y la concepción de extensión rural con que guían su práctica. Los encuestados describen como principales problemas el uso de tecnologías inapropiadas, la falta de créditos y las difi cultades para el trabajo grupal. A nivel general se observa la presencia de una concepción de la extensión fuertemente transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
(9 reference statements)
0
2
0
3
Order By: Relevance
“…These results were replicated when the author carried out the analysis at the national level. In the case of El Salvador, Landini (2015) reported that among producers there are other problems, mainly individualism, mistrust and lack of associations. These are manifested as egotism and lack of organization by the producers, which make difficult the group work necessary for the success of extension projects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were replicated when the author carried out the analysis at the national level. In the case of El Salvador, Landini (2015) reported that among producers there are other problems, mainly individualism, mistrust and lack of associations. These are manifested as egotism and lack of organization by the producers, which make difficult the group work necessary for the success of extension projects.…”
Section: Introductionmentioning
confidence: 99%
“…For this, the following hypothesis was set out: individualism and mistrust keep tomato producers of San Pablo Güilá from becoming organized. In this regard, Landini (2015) suggests addressing the problem from a sociocultural perspective, and this study sought to delve into the behavior of the farmers in order to attain greater comprehension of their intrinsic traits that influence the resistance to becoming part of an association.…”
Section: Introductionmentioning
confidence: 99%
“…106 -126 liderazgo de los extensionistas rurales, así como la importancia del liderazgo para la ejecución de su trabajo de extensionistas. Más recientemente, diversos trabajos realizados por Fernando Landini han investigado a los extensionistas rurales de diversos países latinoamericanos como Uruguay (Landini y Riet, 2015), Brasil (Landini, 2015), Ecuador (Landini y Bianqui, 2014b) Paraguay (Landini, 2012;Landini, Bianqui y Crespi, 2013) Argentina (Landini, 2016b;2016d), El Salvador (Landini, 2015b); así como Latinoamérica en su conjunto (Landini y Bianqui, 2014;Landini, 2016;2016c). El autor realiza sus investigaciones principalmente desde la psicología, particularmente centrándose en las sinergias que pueden existir entre la psicología y la extensión rural.…”
Section: Introductionunclassified
“…El creciente interés en este tipo de investigaciones sobre extensión rural, y particularmente aquellas que abordan las visiones sobre los extensionistas rurales, parece no haber permeado aún en El Salvador. De esa forma, fue posible identificar tan solo un estudio que aborda exclusivamente las percepciones de extensionistas rurales en este país (Landini, 2015b). En el mencionado trabajo, Landini (2015b) se centraba en los problemas enfrentados por extensionistas públicos salvadoreños, queriendo a su vez indagar cuál era su concepción en la extensión rural.…”
Section: Introductionunclassified
See 1 more Smart Citation